(untitled) (Revista de História da UEG (REVHIST), 2020)
All human beings are caught by time, that is, from childhood to elder age, people build different perceptions and experiences that guide their way. The contemporary society seems to avoid the time and its consequences that show the human finitude. This text looks for thinking about the different ways of time experience by elders through the concepts of historicity and temporality. Moreover, this debate does not take off historicization of manners that old age was being built and thought, especially, in Brazilian society. The making of perceptions and of aging is remarkable from vocabulary to practices, there are many ways which subjects give meaning to this process that is inherent to all people and, simultaneously, are affected by a specific historicity regime. Keywords: Contemporary society. Time and temporalities. Aging.